Perbandingan Pemikiran Al-Ghazali dan Ibnu Taimiyah Tentang Amar Ma’ruf Nahi Munkar - Syaiful Dinata; Eva Latipah; Ismatul Izzah (Program studi Keagamaan Islam, 2022)
This research is a study of the Islamic thought of two Islamic figures, namely Al-Gazhali and Ibn Taimiyah, regarding calling for good and preventing from bad (amar ma'ruf nahi munkar). This research is motivated by the difference in thinking of the two scholars regarding (amar ma'ruf nahi munkar). Seeing this phenomenon, a reassessment of amar ma'ruf nahi munkar is very important and urgent to do. The research questions are: how al-Gazhali and Ibn Taimiyah think about amar ma'ruf nahi munkar; and how do the two figures differ and differ in their thoughts on amar ma'ruf nahi munkar? This study aims to describe the thoughts of Al-Gazhali and Ibn Taimiyah about amar ma'ruf nahi munkar, looking for differences and similarities between the two. This research is a literature-based research. The method used is a qualitative descriptive research method. The results showed that the method of practice of amar ma'ruf nahi munkar (especially nahi munkar) compiled by Al-Gazhali was carried out in stages, starting from the mild stage such as notifying the perpetrators of the mundane, to the more violent or decisive stage such as threatening or even hitting. Meanwhile, Ibn Taimiyah, carrying out his practical method, namely the subtle way is the way of amar ma'ruf nahi munkar. Affection is the foothold of amar ma'ruf nahi munkar. Therefore, Ibn Taimiyah taught that in practice goodness (maslahat) must take precedence over ugliness (mafsadhat).